The mystery of oncogenic KRAS: Lessons from studying its wild-type counter part. (2nd October 2017) - Chang, Yuan-I; Damnernsawad, Alisa; Kong, Guangyao; You, Xiaona; Wang, Demin; Zhang, Jing
ABSTRACT: Using conditional knock-in mouse models, we and others have shown that despite the very high sequence identity between Nras and Kras proteins, oncogenic Kras displays a much stronger leukemogenic activity than oncogenic Nras in vivo. In this manuscript, we will summarize our recent work of characterizing wild-type Kras function in adult hematopoiesis and in oncogenic Kras-induced leukemogenesis. We attribute the strong leukemogenic activity of oncogenic Kras to 2 unique aspects of Kras signaling. First, Kras is required in mediating cell type- and cytokine-specific ERK1/2 signaling. Second, oncogenic Kras, but not oncogenic Nras, induces hyperactivation of wild-type Ras, which significantly enhances Ras signaling in vivo. We will also discuss a possible mechanism that mediates oncogenic Kras-evoked hyperactivation of wild-type Ras and a potential approach to down-regulate oncogenic Kras signaling.